Evaluation of Clustering and Multi-hop Routing Protocols in Mobile Ad-hoc Sensor Networks - Jambli, M.N.; Hendrick, A.; Julaihi, A.A.; Abdullah, J.; Suhaili, S.M. (2015)
Mobile ad-hoc sensor networks (MASNETs) have promised a wide variety of applications such as military sensor networks to detect and gain as much as possible about enemy movements and explosions. Most of these applications can be deployed either in static or mobile environment. In static WSNs, the change of sensor nodes topology is normally caused by node failure which is due to energy depletion. However, in MASNETs, the main reason of the topology change is caused by the node movement. Since the sensor nodes are limited in power supply and have a low radio frequency coverage, they are easily losing their connection with neighbours and difficult to transmit their packets towards sink node. The reconnection process from one node to another node consumes more energy that related to control packets. One of the techniques to conserve more energy is through topology management using clustering network. A HEED (Hybrid, Energy-Efficient, Distributed) is one of the clustering algorithm for sensor networks. In HEED, a node is elected to become a cluster head based on its residual energy and its communication cost in its neighbourhood. HEED clusters the network in a constant number of iterations, elects cluster heads that are well-distributed in the network, and incurs low message and communication overhead. In this research work, through extensive simulation we evaluated the capability of HEED on how far it can react to network topology change in MASNETs by comparing its performance with Surge multihop routing protocol in both static and mobile environment. We investigated the performance of both HEED and Surge in terms of the average percentage of packet loss and the average total energy consumption with various simulation times. From the detailed simulation results and analysis, HEED performs better than Surge in term of energy consumption in static network, but not performs as expected in mobile environment.